A Rare Presentation of Fibromuscular Dysplasia: Postpartum Vascular Catastrophe and Brief Literature Review - Fatima Khan MD; Ali Raza Ghani MD; Larami Mackenzie MD; Ashwin Matthew MD; Usman Sarwar MD; Bruce Klugherz MD (SAGE Publishing, 2017)
Spontaneous coronary artery dissection is a very rare cause of acute coronary syndromes and can be life threatening given the rarity of the condition. It should be part of differentials in young females presenting with acute coronary syndromes without routine risk factors for coronary artery disease, especially before, during, and after pregnancy. It is closely associated with fibromuscular dysplasia and management can be very challenging at times. We present a case of spontaneous coronary artery dissection presenting with recurrent ST segment elevation myocardial infarction in association with fibromuscular dysplasia.